Moda Transportasi sebagai Daya Tarik Wisata yang Menghadirkan Memorable Tourism Experience - Abdul Khoir, Mochammad Henfi (Universitas Persatuan Islam, 2024)
Post-pandemic global tourism trends show a shift from mass tourism to experiential tourism, where tourists seek authentic experiences, one of which is using modes of transportation. This research uses a qualitative approach with a systematic literature review. The research objective is to build a holistic understanding of the role of transportation as a tourist attraction through a literature synthesis. The research results show that modes of transportation can act as tourist attractions when designed to create unique, emotional, interactive, aesthetic and meaningful experiences. By integrating these elements, transportation becomes not only a means of mobility, but also part of a Memorable Tourism Experience (MTE) that enriches a tourist's journey.